Microenvironment modulation of TiO2 nanosheets for highly selective photocatalytic CO2 reduction - Xingxing Zheng; Jun Yang (Química Nova)
Photocatalytic reduction of CO2 and H2O into valuable fuels is a promising and sustainable approach. Phosphate is crucial for the production of ATP (adenosine triphosphate), highlighting its significance in the transfer of energy essential for life. In this study, we design and prepare a modified TiO2 surface with phosphate to reduce CO2 using light. The TiO2+PO43- composite performs exceptionally well, producing CO at a rate of 36.93 μmol g-1 h-1, which is three times higher than pure TiO2, with nearly 100% selectivity for CO. Both experiments and theoretical analyses show that the phosphorus species create a channel for electron transfer between PO43- and Ti, improving charge movement. Modification by phosphate ions (PO43-) alters the surface microenvironment of TiO2, making it easier for more water molecules to be adsorbed on the surface. Furthermore, the PO43- modification adds more oxygen-containing functional groups to the surface. These groups act as sites that help in capturing and activating CO2. As a result, TiO2+PO43- stands out as a strong candidate for CO2 reduction, thanks to better charge transfer and more active sites.